Translating “Reclaiming Realism for the Left: Gar Alperovitz and the Decision to Use the Atomic Bomb” by Peter N. Kirstein with commentary on the translation process and the use of CAT Tools in a professional work environment - (:unkn) unknown (My University, 2018)
In this paper I will analyse and comment on the translation of the following article by Peter N, Kirstein: “Reclaiming Realism for the Left: Gar Alperovitz and the Decision to Use the Atomic Bomb”. I will document the entire translation process, starting with the source file and the hypothetical customer’s notes, through to the translation process itself, using SDL’s Trados Studio and finally to exporting and correcting the file in its end-format.
Translating “Reclaiming Realism for the Left: Gar Alperovitz and the Decision to Use the Atomic Bomb” by Peter N. Kirstein with commentary on the translation process and the use of CAT Tools in a professional work environment
Keywords: Kirstein, ατομική βόμβα, Alperovitz, ρεαλισμός; Kirstein, atomic bomb, Alperovitz, realism